2020
DOI: 10.1007/s11033-020-05349-y
|View full text |Cite
|
Sign up to set email alerts
|

The journey of Zika to the developing brain

Abstract: Zika virus is a mosquito-borne Flavivirus originally isolated from humans in 1952. Following its re-emergence in Brazil in 2015, an increase in the number of babies born with microcephaly to infected mothers was observed. Microcephaly is a neurodevelopmental disorder, characterised phenotypically by a smaller than average head size, and is usually developed in utero. The 2015 outbreak in the Americas led to the World Health Organisation declaring Zika a Public Health Emergency of International Concern. Since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 154 publications
(197 reference statements)
0
16
0
1
Order By: Relevance
“…Similarly, a human STAT2 knock-in, immunocompetent mouse model shows that a mouse adapted ZIKV strain belonging to African lineage was able to cross the placental barrier and blood-brain barrier [35]. Therefore, transplacental route of transmission from mother to the fetus plays a crucial role in the disease process [36,37]. In our previous study, we showed that ZIKV induces a caspase-dependent trophoblast apoptosis as evidenced by significant increase in percent apoptotic nuclei and caspase 3/7 activation following ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a human STAT2 knock-in, immunocompetent mouse model shows that a mouse adapted ZIKV strain belonging to African lineage was able to cross the placental barrier and blood-brain barrier [35]. Therefore, transplacental route of transmission from mother to the fetus plays a crucial role in the disease process [36,37]. In our previous study, we showed that ZIKV induces a caspase-dependent trophoblast apoptosis as evidenced by significant increase in percent apoptotic nuclei and caspase 3/7 activation following ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, peripheral blood mononuclear cells were identified as important cellular targets of American ZIKV strain infection, and for promoting ZIKV spread 39 . It is important to note that astrocytes are functional elements in the BBB, thus these cells can contribute to propagation and progress of ZIKV infection, causing injury of neural cells through direct infection-induced and/or indirect immune-mediated mechanisms 40 42 .…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV caused globally widespread infections in regions hospitable to insect vectors in 2015-2016. During this crisis, children of thousands of pregnant women suffered profound neurodevelopmental damage related to ZIKV crossing the placenta and infecting embryonic brain cells (26). This has led to great interest in vaccine development, with a principle goal of high-titer neutralizing Ab (11).…”
Section: Discussionmentioning
confidence: 99%